Pengaruh Manajemen Keuangan dan Gaya Hidup Terhadap Penggunaan Platform E-Commerce Paylater di Kota Bandung (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the influence of financial management and lifestyle on the use of the Paylater e-commerce platform in Bandung City. The population in this study is Gen Z and Millennials in Bandung City. A quantitative approach method was used in this study, with primary data collection carried out through questionnaires filled out by respondents using Google Forms. This study used a purposive sampling technique in sampling. By using the Slovin formula, the number of samples determined was 342 respondents and for data analysis the author used SPSS 30. The results of this study indicate that Financial Management and Lifestyle have a significant effect on the use of the Paylater e-commerce platform. Additionally, Financial Management has a significant effect on the use of the Paylater e-commerce platform, and Lifestyle also has a significant effect on the use of the Paylater e-commerce platform.